2006
DOI: 10.1007/s10460-005-6107-4
|View full text |Cite
|
Sign up to set email alerts
|

Is HACCP Nothing? A Disjoint Constitution between Inspectors, Processors, and Consumers and the Cider Industry in Michigan

Abstract: The transmission of a product or idea from one culture or point of origin to another and the maintenance of control outside the new locality has been referred to as the distribution and maintenance of ''nothing.'' This perspective has been used to describe the global marketplace and the influence of large multinational corporations on the politics and cultures of host countries. This paper uses this concept, but within a much smaller context. Using the sensitizing concept of a ''disjoint constitution,'' we int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This implies to say that it aims to identify, assess and control hazards during production, processing, manufacturing, preparation, and use of food to ensure its safety when consumed [48]. Apart from management tools used to assure food safety, the focus of quality assurance schemes has become more comprehensive approaches allowing the assurance and safeguarding of process standards, relating for instance to animal welfare and certified production methods such as organic or Halal [20] [52]. In this respect, Halal Assurance System (HAS) is presented as an internal mechanism to monitor, control, improve and prevent any non-compliance in Halal production [53].…”
Section: The Application Of Haccp In Halal Meat Supply Chainmentioning
confidence: 99%
“…This implies to say that it aims to identify, assess and control hazards during production, processing, manufacturing, preparation, and use of food to ensure its safety when consumed [48]. Apart from management tools used to assure food safety, the focus of quality assurance schemes has become more comprehensive approaches allowing the assurance and safeguarding of process standards, relating for instance to animal welfare and certified production methods such as organic or Halal [20] [52]. In this respect, Halal Assurance System (HAS) is presented as an internal mechanism to monitor, control, improve and prevent any non-compliance in Halal production [53].…”
Section: The Application Of Haccp In Halal Meat Supply Chainmentioning
confidence: 99%
“…In addition, differences in perspectives between inspectors and food business owners on food safety-related issues have been documented. Eyck et al [ 4 ] revealed that inspectors’ views on HACCP implementation were not in accordance with those of many of the apple cider processers in Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…The food industry is challenging to regulate because it is dynamic and flexible. A recent trend is for food businesses to cross over between retailing and manufacturing, blurring the lines between industries [2][3][4][5]. For example, a retail food establishment may start focusing on selling food directly to consumers with a side revenue of selling to other businesses.…”
Section: Introductionmentioning
confidence: 99%
“…How to ensure food hygiene and the safety of teachers and students in colleges and universities, and prevent and eliminate the recurrence of food poisoning and food-borne diseases for teachers and students? Therefore, the certification system has become popular in China, and the prevalent standards and management models for food safety in Chinese universities include the quality management system, HACCP (Eyck et al, 2006;ISO, 2018), quantitative and hierarchical management of catering industry hygiene supervision, "5S" and "6T" (Fang, 2005).…”
Section: Current Status Of Catering Quality In Canteens In Chinamentioning
confidence: 99%